ANALISIS STABILITAS TIMBUNAN PROYEK PEMBANGUNAN JALUR GANDA JALAN KERETA API (KA) SEPANJANG-MOJOKERTO - Wulan Anggarita, Ovilia; Putra Purnama, Paksitya; Nurtjahjaningtyas, Indra; Trisno Lestari, Rini (Politeknik Negeri Jakarta, 2024)
The construction of the Sepanjang-Mojokerto railway double track is an initiative to address the growing demand for railway transportation infrastructure. During the building of the double-track railroad, it is anticipated that the rail structure will endure the weight of traversing trains; hence, a stability study for settlement and sliding is essential. The settlement of the embankment between KM 49+500 and KM 49+750 was studied using sondir and borlog correlation data and then a geoslope model to see how stable the embankment was against sliding. The calculated findings indicate a reduction of 0.49 m to 1.49 m. The decrease is unsafe as it is above the permissible limit of 20 cm; achieving a decline to U90% requires around 0.9 years—15 years. Consequently, it is imperative to expedite the reduction using PVD and preloading. The PVD installation employs a triangle configuration with a spacing of 1.5 meters, requiring a duration of 16 to 20 weeks to achieve a 90% reduction. The stability control of the embankment against sliding on the railroad body yielded a safety factor (SF) value ranging from 1.63 to 2.33. SF > 1.5 indicates that the SF value is secure, surpassing the permissible threshold.